Lies (people believe) About Animals - Sussman, Susan; Leavitt, Fred (Niles : Albert Whitman & Company, 1987)
Presents commonly held beliefs abouts bats, tarantulas, snakes, porcupines, and other animals and then explains the surprising truths.
Keywords: animals-Miscelllanea -- Juvenile Literature